Influence of Substances Abuse on Academic Performance of Secondary School Students: A Study of Government Day Secondary School Nukkai, Jaligo Local Government Area, Taraba State, Nigeria - Tifkwah, Tifkwah James; Moses, Abigail Embwa (International Journal of Research in Interdisciplinary Studies, 2025)
This study investigates the influence of substance abuse on the academic performance of secondary school students at Government Day Secondary School Nukkai, Jalingo Local Government Area, Taraba State, Nigeria. The increasing prevalence of substance abuse among adolescents has raised concerns about its impact on students' educational outcomes. The study's problem centers around the growing rates of substance abuse among students and its potential consequences on their academic performance. This issue is compounded by socio-economic factors, such as financial instability and peer pressure, which influence students' decisions to engage in substance use. Additionally, the proximity of substances to the school environment further contributes to the challenge. A descriptive research design was adopted, utilizing a combination of surveys and interviews to gather data from students and school staff. The study revealed that 40% of students reported poor academic performance, which was attributed to the negative effects of substance abuse, including difficulties in concentrating and frequent absenteeism. Socio-economic factors and peer pressure were identified as significant influences on students' substance use behaviors, while the availability of substances near the school environment was also a key contributing factor. In conclusion, the study underscores the negative impact of substance abuse on academic performance among students at Government Day Secondary School Nukkai. To address this issue, the study recommends the implementation of awareness programs, stricter school policies, counseling services, and active parental involvement. Additionally, expanding extracurricular activities to engage students in positive alternatives is crucial. A collaborative, multi-faceted approach involving students, parents, teachers, and policymakers is necessary to effectively combat substance abuse and improve academic outcomes in the school.